Nurse Engagement and Contributions to the Clinical and Translational Science Awards Initiative - Sampselle, Carolyn M. (John Wiley and Sons Inc., 2013)
CTSAs are mandated to follow a multidisciplinary model. Requests for applications direct responsive applications to “integrate clinical and translational science across multiple departments, schools,” listing disciplines in addition to medicine such as engineering, nursing, and public health. This inventory of nurse engagement in CTSAs describes the extent of nursing's CTSA engagement from the perspective of participating nurse scientists within individual CTSAs, including institutional/national contributions and best practices that foster a multidisciplinary model. Of the 50 CTSAs affiliated with a nursing school, 44 responded (88% response rate). Of the ten CTSAs not affiliated with a nursing school, four responded (40% response rate). Overall funding success rates of nurse applicants are: TL1 fellowships 81%, KL2 fellowships 54%, and nurse‐led pilots 58%. At most CTSAs nursing is contributing to the accomplishment of the CTSA mandate. The strongest categories of contribution are community engagement, implementation science, and training. Best practices to enhance multidisciplinary collaboration are: (1) inclusion of multiple disciplines on key committees who meet regularly to guide individual core and overall CTSA strategic planning and implementation; (2) required multidisciplinary co‐mentors (ideally from different schools within the CTSA) on training grants and as co‐investigators on pilot projects; and (3) documentation of multidisciplinary activity in annual reports.